Multiobjective variational problems with time delay. Issue 7 (18th May 2020) - Malinowska, Agnieszka B.; Odzijewicz, Tatiana
Abstract : In this paper, the study of multiobjective variational problems with time delay is introduced. We provide methods for identifying Pareto optimal solutions. We also prove necessary and sufficient optimality conditions for the isoperimetric problem with multiple constraints and delayed arguments.